2014
DOI: 10.1155/2014/149195
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 Protects Neonatal Rat Cardiomyocytes from Hypoxia/Ischemia Induced Apoptosis and Inhibits Activation of the Mitochondrial Apoptotic Pathway

Abstract: Aim. To investigate the effect of Ginsenoside Rb1 (GS-Rb1) on hypoxia/ischemia (H/I) injury in cardiomyocytes in vitro and the mitochondrial apoptotic pathway mediated mechanism. Methods. Neonatal rat cardiomyocytes (NRCMs) for the H/I groups were kept in DMEM without glucose and serum, and were placed into a hypoxic jar for 24 h. GS-Rb1 at concentrations from 2.5 to 40 µM was given during hypoxic period for 24 h. NRCMs injury was determined by MTT and lactate dehydrogenase (LDH) leakage assay. Cell apoptosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Microglial apoptosis is more detrimental than microglial activation in response to inflammatory challenge . The neuroprotective effects of Rb1 have been confirmed in several studies; however, the mechanism of Rb1 interacting with microglia is largely unknown . Thus, we evaluated the ability of Rb1 to affect microglial apoptosis in cultured BV2 microglial cells infected with S. pneumoniae .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Microglial apoptosis is more detrimental than microglial activation in response to inflammatory challenge . The neuroprotective effects of Rb1 have been confirmed in several studies; however, the mechanism of Rb1 interacting with microglia is largely unknown . Thus, we evaluated the ability of Rb1 to affect microglial apoptosis in cultured BV2 microglial cells infected with S. pneumoniae .…”
Section: Resultsmentioning
confidence: 98%
“…28 The neuroprotective effects of Rb1 have been confirmed in several studies; however, the mechanism of Rb1 interacting with microglia is largely unknown. 29,30 Thus, we evaluated the ability of Rb1 to affect microglial apoptosis in cultured BV2 microglial cells infected with S. pneumoniae. Rb1 treatment significantly increased the expression of ERβ, BDNF ( Figure 3A notably, these mRNA changes occurred prior to significant alterations in protein.…”
Section: Rb1 Promotes Bcl-2/bcl-xl Expression In Microglia Via the Erβmentioning
confidence: 99%
“…However, both the anti-apoptotic and antiproliferative capacities of ginsenoside Rb1 on different cell types under diverse pathological conditions were reported previously. For instance, ginsenoside Rb1 reduced ischemia/reperfusion-induced apoptosis of cardiomyocytes and neurocytes [39,40], while the anticancer property of ginsenoside Rb1 was exhibited through its inhibition of melanoma cell proliferation [41]. Li et al [42] demonstrated that ginsenoside Rb1 inhibited FBS-induced proliferation of rat aortic smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial apoptotic pathway included loss of ΔΨm and changes in Bcl-2/Bax ratio, which are followed by activation of caspase-3. Once caspase-3 is in action, apoptotic cell death is inevitable (Ly, Grubb, & Lawen, 2003;Yan et al, 2014). The Bcl-2 family, including Bcl-2 and Bax, is the major protein that regulates the mitochondrial pathway by controlling the permeabilization of mitochondrial membrane (Tang et al, 2013;Tomiyama et al, 2010).…”
Section: Discussionmentioning
confidence: 99%